Accounting Treatment of Biological Assets in Plantation Industry on Wetlands (Case Study in Plantation Company Entities in South Kalimantan) - Chairina Chairina; Sarwani Sarwani (Journal of Wetlands Environmental Management, 2018)
The purpose of this study is to determine the Accounting treatment of biological assets based on IAS 41 Agriculture. DSAK-IAI in the process of convergence of PSAK with IFRS states that one of the standards that is still being project remaining work since 2010 is IAS 41. IAS 41 is adopted into PSAK No.69 Agriculture as the Accounting standard that regulates special biological assets that will be effectively applicable on 1 January 2018. The results of this study are expected to provide the description of Accounting treatment based on IAS 41 in more detailed and clear in terms of recognition and presentation and disclosure of biological assets. However, in terms of measurement, IAS 41 will be more difficult to implement because the market price for the plantation industry has not been able to be a benchmark of fair value.       This research was a qualitative descriptive research by giving a description of the Accounting treatment of biological assets engaged in oil palm plantation. Data collection techniques used questionnaires sent to the company with 10 (ten) samples of oil palm companies representing Banjarmasin City, Banjarbaru City, Banjar Regency, Tapin Regency and Tanah Laut regency. The data were analyzed by using descriptive analysis and index calculation of implementation conformity to the standard.        The results showed that the companies have applied the Accounting treatment of biological assets on the average of 90.8% based on research indicators. In terms of classification the companies have classified 100% of its biological assets well. Recognition, measurement and assessment of biological assets, the companies applied research indicators in the range of 84% - 97%, this condition was caused more because the basis of valuation with the fair value of biological assets was not readily available in the active market thus affecting the recognition, measurement and valuation of those assets. While Presentation and Disclosure of Biological Assets in the financial statements, the companies applied 77.5% - 96% of the existing disclosure indicators.